ANALISIS PERBANDINGAN ISI BUKU TEKS MATA PELAJARAN SOSIOLOGI KELAS XI SEMESTER I TERBITAN ERLANGGA DAN YUDHISTIRA - Febrina, Renno - (Pendidikan Sosiologi, 2014)
Textbooks are obligation to use a reference book that contains school learningmaterials in order increase faith and piety of character and personalitiy abilities. Mastery ofscience and technology sensitivity and aesthetic, health physical potential which is based onnatural education standar. At the present time a wide range of the textbooks published byvarious publisher. But in the fact found textbooks that have not met the requipments, becauseof diference in the description of the learning materials provided by the textbook.Explanation of the concept of matter that is not accompained by the material fact and thequestion or tasks assigned textbook is not contained in the learning materials.The teory used is cognitivism by Wilhem Wundt, behaviorism by B.F Skinner, andsocial action by Max Weber. This study used a qualitative research approach with a typeliterary study. The object of this research is the sociology textbooks published by Erlanggaand Yudhistira. Data collected by study of literature. Data analysis used content analysistechniques.The result of the study are 1) Completenes of the basic concepts of the matter and thetype of material on the sociology textbook published by Erlangga and Yudhitira, each ofthese books have same advantages and disadvantages in the description of the material. 2) thecompatibility of the question presented by the findings of the field data showed that thetextbooks published by Erlangga and Yudhistira contains question that are not relevan withthe material decribed in the discussion.